DisCrit expanded : reverberations, ruptures, and inquiries - Annamma, Subini A.; Ferri, Beth A., 1961-; Connor, David J., 1961- (Disability, culture, and equity series., 2022)
"The grounding assumption that undergirds Disability Critical Race Theory (DisCrit) is that racism and ableism are mutually constitutive and collusive-always circulating across time and context in interconnected ways. Through we originally wrote DisCrit in 2013 and have written a number of projects with it as the foundation, DisCrit rapidly expanded far beyond our own work. In tracing this reverberation, we are struck by the ways DisCrit has been taken up, expanded upon, and used as a jumping off point for further creative articulations. The dynamic landscape of scholarship taking up DisCrit reflects its role in fostering a transgressive space that has generated critical questions looking outward, inward, and across differences and divides. Following an introduction by a, intellectual forerunner to DisCrit, Alfredo Artiles, is a three-part edited book organized around central inquiries that are directed outward, inward, as well as across or margin-to-margin. Through each section, authors answer these central inquiries by applying DisCrit across theoretical, methodological, and analytical spaces to shift praxis, exploring who we are answerable to axiologically, and expanding beyond missing pieces or silences associated with DisCrit. The closing chapter synthesizes ruptures, including issues raised and explored in the present text, and look toward the future of how DisCrit can be useful in developing more complex understandings of inequalities with view to working toward countering them in different, yet interconnected, levels including: the personal, the professional, and the structural"--